Cytoreductive surgery for advanced and recurrent endometrial cancer: a review of the literature. (July 2009) - Barlin, Joyce N; Ueda, Stefanie M; Bristow, Robert E
There is no standard approach to managing women with advanced or recurrent endometrial cancer; however, there is increasing evidence to support a role for cytoreductive surgery in these women to improve survival outcome. The existing literature is limited by the inherent biases of retrospective studies, as well as small numbers of patients in individual studies; however, the association between optimal or complete cytoreductive surgery in patients with advanced and recurrent endometrial cancer and improved overall survival has been consistent. Furthermore, there is also a strong association between the size of postoperative residual disease and survival; as such, maximal cytoreduction should be the goal in carefully selected patients with advanced or recurrent endometrial cancer who are candidates for surgical management. Additional prospective research is needed in order to further define the role of cytoreductive surgery in advanced and recurrent endometrial cancer, and to develop effective adjuvant therapy to be used postoperatively in order to improve the prognosis in these women.